Globalization, pass-through and inflation dynamic - Pierpaolo Benigno; Ester Faia (Kiel Institute for the World Economy (IfW), 2010)
An important aspect of the globalization process is the increase in interdependence among countries through the deepening of trade linkages. This process should increase competition in each destination market and change the pricing behavior of firms. We present an extension of Dornbusch (1987)'s model to analyze the extent to which globalization, interpreted as an increase in the number of foreign products in each destination market, modifies the slope and the position of the New-Keynesian aggregate-supply equation and, at the same time, affects the degree of exchange-rate pass-through. We provide empirical evidence that supports the results of our model. ; An important aspect of the globalization process is the increase in interdependence among countries through the deepening of trade linkages. This process should increase competition in each destination market and change the pricing behavior of firms. We present an extension of Dornbusch (1987)'s model to analyze the extent to which globalization, interpreted as an increase in the number of foreign products in each destination market, modifies the slope and the position of the New-Keynesian aggregate-supply equation and, at the same time, affects the degree of exchange-rate pass-through. We provide empirical evidence that supports the results of our model
Keywords: 330; Globalisierung; Inflationsübertragung; Exchange Rate Pass-Through; New-Keynesian Phillips Curve; Schätzung; USA